A study of lipid profile in chronic kidney disease in pre- dialysis patients - Nitin Choudhary (International Journal of Medical Research and Review, 2019)
Introduction: Longitudinal studies have established that Cardiovascular Disease (CVD) occur more frequently and are the leading cause of death in Chronic Kidney Disease (CKD). Dyslipidemia has been established as an important risk factor in the pathogenesis of CVD in CKD patients.Objectives: Present study was aimed to evaluate (in CKD patients),Demography along with Prevalence and Pattern of Dyslipidemiaand co-relation of Dyslipidemia with various CK Dstages. Methods: Present Cross-sectional study, conducted in Department of Medicine, R.D. Gardi Medical College and CRG hospital, Ujjain, M.P. from 1st January 2015 to 31st July 2016.We studied 115 pre-dialysis CKDcases and 100 age & sex matched controls. CKD was diagnosed as per 2012 KDOQI Criteria.Result:In CKD cases,maximum 23.47% cases belonged to fifth decade. Mean age was 48.99 ± 16.74. Male to Female ratio was1.21: 1. Prevalence of individual dyslipidemias was High TC= 50.44%, High TG= 67%, High LDL-C= 42%, High VLDL-C= 67% and Low HDL-C= 73.9%. Overall, prevalence of dyslipidemia was 82.6%. Significant increase in TG and VLDL-C and significant decrease in HDL-C was observed. TC and LDL-C were non- significantly increased.TC, TG, LDL-C and VLDL-C were in increasing trend with progression of CKD stages (3-5) and increased in Subgroup II (ESRD) as compared to Subgroup I (Non-ESRD), the increase being significant in case of TG and VLDL-C. HDL-C value was in decreasing trend with progression of CKD stages and significantly decreased in Subgroup II as compared to Subgroup I.TC, TG, LDL-C and VLDL-C showed negative correlation with GFR while HDL-C showed positive correlation. TG, HDL-C and VLDL-C showed highly significant correlation. HDL-C showed strongest correlation, followed by TG.Conclusion: Patients with CKD are predisposed to accelerated atherosclerosis leading to increased CVD. This study confirms the presence of atherogenic lipid profile in CKD.